Professional Competency Analysis of Physical Education Teachers at The Level of Private Madrasah Ibtidaiyah Based on Government Regulation Number 19 of 2017 - Fatkhur Rozi; Yudhi Purnama; Abdul Aziz Purnomo Shidiq (Al-Aulad: Journal of Islamic Primary Education, 2022)
Physical education (PE) is one of the subjects taught at the Elementary School or Madrasah Ibtidaiyah (MI) level. Physical education has an important role in meeting the needs of movement, maintaining physical fitness, and creating a healthy lifestyle for MI students. The achievement of physical education learning objectives is certainly influenced by various factors, one of which is the Professional Competence of Physical Education Teachers. This research aims to analyze the Professional Competence of Physical Education Teachers at the MI level. The MI in question is a private sector located in Central Java Province. The research approach is quantitative with survey techniques. The research sample amounted to 30 which were taken at random (simple random sampling). The main data is the Professional Competence of Physical Education Teachers as measured by one of the main indicators, namely professional education in accordance with Government Regulation of the Republic of Indonesia Number 19 of 2017 Article 1 Paragraph 2 and 4, analyzed descriptively qualitatively. The results of this study are that 87% of Physical Education teachers are Strata One graduates according to the Physical Education/Sports/Sports education clump, 7% are Strata One graduates from other fields of science, 3% are Diploma Two graduates, and 3% are high school graduates, and all of them do not have an Educator Certificate (Penjas). The conclusion of this research is that most of the Physical Education Teachers at Private MI do not have good professional competence because they do not have an Educator Certificate.